The South Atlantic and Transatlantic Slave Trade: Review Essay - Borges,Graça Almeida (2017)
This essay will review two recent books on the transatlantic slave trade, which privilege the Southern Atlantic dynamics of this trade. Centred on the common contributions of both works, this article will address two main issues: firstly, it will reflect upon the southern directions that the study of transatlantic slave trade is experiencing, focusing on the importance of trans-regional and trans-national approaches, and on the importance of African agency; secondly, it will address the operational capacities of the Trans-Atlantic Slave Trade Database to the field, thoroughly used in both volumes, which will serve as an excuse to briefly reflect upon the importance of Digital Humanities as a whole